2017
DOI: 10.4048/jbc.2017.20.4.378
|View full text |Cite
|
Sign up to set email alerts
|

Improved Model for Predicting Axillary Response to Neoadjuvant Chemotherapy in Patients with Clinically Node-Positive Breast Cancer

Abstract: PurposePathological complete response (pCR) of axillary lymph node (LN) is frequently achieved in patients with clinically node-positive breast cancer after neoadjuvant chemotherapy (NAC). Treatment of the axilla after NAC is not well established and the value of sentinel LN biopsy following NAC remains unclear. This study investigated the predictive value of axillary response following NAC and evaluated the predictive value of a model based on axillary response.MethodsData prospectively collected on 201 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…To efficiently select the patients who would benefit from SLNB after NAC, many studies have been performed (8)(9)(10)(11)(12)(13)(14)(15). Some studies included initial clinical T or N stage in their model without consideration of residual LN metastasis after NAC (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…To efficiently select the patients who would benefit from SLNB after NAC, many studies have been performed (8)(9)(10)(11)(12)(13)(14)(15). Some studies included initial clinical T or N stage in their model without consideration of residual LN metastasis after NAC (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…According to the study by Osorio-Silla [77], 59.7% of patients with primary lesions complete response on MRI also achieved complete response on axillary lymph node, and 75.9% of patients with non-complete response of breast primary tumors on MRI had residual lymph node disease after surgery. Many studies [104,106,107] have similar results, indicating the importance of MRI complete response in primary lesion rate is an important independent for predicting of axillary pCR.…”
Section: Lymph Node Response Evaluationmentioning
confidence: 67%
“…But the post-NAT MRI obtained a high negative predictive value (94% and 97.3%, respectively), which means that negative post-NAT MRI can accurately exclude the axillary lymph node diseases [101,102]. Before and during NAT, lymph node pCR can be predicted by negative hormone receptor and positive HER2 receptor status [103][104][105], lower clinical T and N stage [103], higher histological/nuclear grade [103], and treatment response to NAT of breast primary lesions [106,107]. According to the study by Osorio-Silla [77], 59.7% of patients with primary lesions complete response on MRI also achieved complete response on axillary lymph node, and 75.9% of patients with non-complete response of breast primary tumors on MRI had residual lymph node disease after surgery.…”
Section: Lymph Node Response Evaluationmentioning
confidence: 99%
“…Several groups have found that adding MRI response of the primary tumor to clinicopathologic data achieves significantly better predictive power. [74][75][76][77] Ha et al trained an artificial intelligence algorithm to predict pCR in the axilla based on pretreatment MRI of the in-breast tumor alone, achieving an overall accuracy of 83%. 78 These models could improve prediction of axillary disease and allow better preoperative planning and patient counseling regarding surgical and radiation options.…”
Section: Lymph Node Evaluationmentioning
confidence: 99%
“…Negative hormone receptor and positive HER2 receptor status, lower clinical T and N stages, high histologic/nuclear grade, and breast tumor response to neoadjuvant therapy are predictors for axillary pCR. Several groups have found that adding MRI response of the primary tumor to clinicopathologic data achieves significantly better predictive power 74–77 . Ha et al trained an artificial intelligence algorithm to predict pCR in the axilla based on pretreatment MRI of the in‐breast tumor alone, achieving an overall accuracy of 83% 78 .…”
Section: Lymph Node Evaluationmentioning
confidence: 99%